SOCIAL STIGMA AND CONSTRUCTION OF EDUCATED UNEMPLOYMENT: A CASE STUDY IN SURABAYA - Artha, Gratia Wing (jfpublisher, 2023)
The number of unemployed people with undergraduate education has increased quite rapidly from previous years. It is estimated that thirty percent (30%) of university graduates cannot get the job based on their expertise. This research aims to explain the condition of fresh graduates from top universities who are forced to become educated unemployed. The results of this research are also expected to contribute ideas related to employment issues which are currently become the social problems for numerous fresh graduates. This research is using a qualitative method that explores and provides deeper insights into real-world problems through examining participants’ experiences, perceptions, and behavior. This research describes the phenomenon of educated unemployment in Surabaya, that they are forced to accept the status of educated unemployed due the intense job competition and minimum of job vacancy. Based on research result, it was found that fresh graduates faced several obstacles in finding the opportunities for limited job vacancies. From this, it can be ascertained that not all fresh graduates can get the work based on their expertise, and most of fresh graduates have to receive an unexpected status as educated unemployed group for no specified time period. In addition, the high expectation from family and society for fresh graduates makes them become more depressed.